A remote marking device and newly developed permanent dyes for Wildlife research - Patricia Baird; Dan Robinette; Scot A. Hink (Wildlife Society Bulletin)
ABSTRACT Noninvasive, safe, quick marking of individual animals using distinctive colors that are highly visible and persistent is a valuable methodology, but practical techniques and permanent safe dyes are lacking. Here we describe a novel, remotely controlled dye machine to rapidly mark stationary animals in predictable locations, such as birds sitting on nests on the ground or mammals at a den or burrow site. From the month of June when birds were on eggs, using the machine, we spot‐dyed 77 California least terns (Sternula antillarum browni) at a colony in California, USA, in 4 days without handling them. Concomitantly, we developed a suite of permanent (until molt or shedding), mainly phthalocyanine dyes that are incorporated chemically into feathers or fur of animals and cannot be preened or rubbed off, which have never been used before to dye animals. We found no toxicity of the dyes during in vivo testing over 1 month. This method of remote marking with permanent dyes should prove to be a useful method in animal ecology for distinguishing among individuals with minimal disturbance. © 2017 The Wildlife Society.